Dynamic Process Integration Framework: Toward Efficient Information Processing in Complex Distributed Systems - Pavlin, G.; Kamermans, M.; Scafes, M. (Informatica)
Dynamic Process Integration Framework: Toward Efficient Information Processing in Complex Distributed Systems